GAMBARAN KECEMASAN MAHASISWA JURUSAN KEPERAWATAN DALAM MENYUSUN SKRIPSI - Lenora Samkakai (Jurnal Ilmiah Keperawatan, 2023)
The results of a preliminary study conducted by researchers showed that 4 people expressed confusion in developing existing theories, where to start working, 4 people lacked knowledge in writing, did not understand where to start, 5 people expressed difficulty in determining the title or theme to be taken in Putting together a sentence, 3 people stated that they had perceptions such as feeling afraid to carry out guidance with the thesis supervisor due to not being able to understand what would be taken up in the research, 4 people stated that they had low motivation in working on their thesis due to internal and external factors. This research aims to determine the picture or perception of anxiety in final semester students when writing their thesis. This research uses a quantitative descriptive design to determine the picture of anxiety of students majoring in nursing when writing their thesis at the Faculty of Health, Sari Mulia University. The characteristics of the respondents in this study were based on age, the most respondents were 21 years old, 12 respondents, 10 respondents aged 22 years, 3 respondents aged 23 years, and at least 24 years old, 5 respondents. The gender of students who experienced anxiety about working on their thesis at the Faculty of Health, Undergraduate Nursing Study Program, was 6 respondents male and 24 female respondents. Of the 30 respondents who took part in this study, 3 respondents (10.0%) experienced mild anxiety, 16 respondents (53.3%) experienced moderate anxiety, 8 respondents (26.7%) experienced severe anxiety and very weight as many as 3 respondents (10.0%). Keywords: Description of anxiety, students, thesis